2006
DOI: 10.1093/geronb/61.5.s274
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Assistive Device Use on Disability and Depression Among Older Adults With Age-Related Vision Impairments

Abstract: We propose that these differential effects result from the fact that optical devices optimize residual vision and thus allow for greater continuity in the way tasks are accomplished (i.e., reading still performed visually), whereas use of adaptive aids (e.g., talking books) involves learning new methods in order to compensate for lost functions and thus is not as desirable either functionally or psychologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 39 publications
2
65
1
Order By: Relevance
“…69,93,100,107 Although clinical outcomes are important, they do not necessarily reflect the abilities that the patients will show in their home environment; for example, a large discrepancy has been demonstrated between individuals with a good near VA in the clinic (75%), and those able to resolve small print at home (39%). 93 From this review, it was apparent that in the past decade there has been a drive towards assessing outcomes based on measures of ability and/or independence in performing daily tasks, 48,65,110 on measures of psychological status, 52,72,75 or on patient-reported quality-of-life. 43,70,91,115 Instruments assessing functional status may be scored entirely based on a patient's judgment of their own ability (self-report/patient-rated assessment), e.g.…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
See 4 more Smart Citations
“…69,93,100,107 Although clinical outcomes are important, they do not necessarily reflect the abilities that the patients will show in their home environment; for example, a large discrepancy has been demonstrated between individuals with a good near VA in the clinic (75%), and those able to resolve small print at home (39%). 93 From this review, it was apparent that in the past decade there has been a drive towards assessing outcomes based on measures of ability and/or independence in performing daily tasks, 48,65,110 on measures of psychological status, 52,72,75 or on patient-reported quality-of-life. 43,70,91,115 Instruments assessing functional status may be scored entirely based on a patient's judgment of their own ability (self-report/patient-rated assessment), e.g.…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
“…33,69,70,115,121,122,124 Validity of low vision aid usage as a surrogate for service effectiveness is supported by the findings of Horowitz et al, who reported that the use of LVAs is associated with a reduction in disability and depression at 6 months. 72 The Manchester Low Vision Questionnaire (MLVQ) has been used as a standardised tool to assess aspects of LVA usage and satisfaction. 70,115,122,124 For example, Reeves et al used the MLVQ as an outcome measure in following up 226 patients for up to 1 year after provision of 3 different service models, and showed that patients valued their LVAs highly, and showed a high use of LVAs throughout the trial, despite apparently negative outcomes in vision-related QoL and QoL domains.…”
Section: B Frequency Of Use Of Lvas Following Low Vision Service Intmentioning
confidence: 99%
See 3 more Smart Citations